Digital Property and New Economic Relations - O. N. Grabova; A. E. Suglobov (Финансы: теория и практика)
Modern economic relations are developing under the influence of digital property that creates conditions for unprecedented socialization of production and new realities in the relations of appropriation and alienation. This requires both theoretical interpretation and practical research. The aim of the article is to identify current trends in the development of digital property and the new economic relations that it forms in the world, to systematize the conditions for digital property in Russia. The authors used the findings of institutional and evolutionary economic theories, political economy, as well as the principles and methods of SWOT-analysis in order to systematize the issue. The paradigm of the development of Russia should be changed from consumption to production of innovative products and technologies of the digital economy. The paper presents the essential characteristics of digital property and a model of the influence of the digital economy and global integration on modern economic relations. Potential opportunities for the economic development in the system of new economic relations were identified due to the SWOT-analysis of the conditions for the development of digital property in Russia. At the same time, endogenous institutional and target restrictions on the development of the digital economy in Russia (as weaknesses), as well as exogenous restrictions in the form of threats were specified. The authors found the strategic modeling of systems engineering education as a long-term basis for the development of the digital economy necessary. The research results can be used in developing national programs.